Negative gravitactic behavior of Euglena gracilis can not be described by the mechanism of buoyancy-oriented upward swimming. - Lebert, Michael; Häder, Donat-Peter (Advances in Space Research, 1999)
Gravitactic behavior of microorganisms has been known for more than a hundred years. Euglena gracilis serves as a model system for gravity-triggered behavioral responses. Two basic mechanisms are discussed for gravitaxis: one is based on a physical mechanism where an asymmetric mass distribution pulls the cell passively in the correct orientation and, in contrast, the involvement of an active sensory system. A recently developed high-resolution motion-tracking system allows the analysis of single tracks during reorientation. The results are compared to a model developed by Fukui and Asai (1985) which describes gravitaxis of Paramecium caudatum on the basis of a physical mechanism. Taking into account the different size, different density, different mass distribution as well as the different velocity, results of the adapted model description of Paramecium were applied to measured data of Euglena. General shapes as well as the time scale of the predicted reorientational movement compared to measurements were different. The analysis clearly rules out the possibility that gravitaxis of Euglena gracilis is based on a pure physical phenomenon, and gives further support to the involvement of an active reorientational system. In addition, it could be shown that cell form changes during reorientation, even in an initial period where no angular change was observed. © 1999 COSPAR. Published by Elsevier Science Ltd.
UnivIS-Import:2015-03-05:Pub.1999.nat.dbio.LBIPDH.negati